1980
DOI: 10.1063/1.327424
|View full text |Cite
|
Sign up to set email alerts
|

Trans-gauche concentration in crystalline polyethylene measured by the intensity of rocking mode vibrations of deuterated methylene groups

Abstract: Polyethylene with a low concentration of deuterated methylene groups displays an infrared band in the frequency region 646–651 cm−1. This band is attributed to a rocking normal mode of a CD2 group with one of the adjacent dihedral angles approximately trans and the other approximately gauche (tg). This mode vibrates at 620 cm−1 when the dihedral angles adjacent to the CD2 group are both trans (tt). In polyethylene crystals tg sequences can occur only in defects where constraints cause some of the dihedral angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The presence of gauche conformations and some sequences of gauche and trans conformations (for example, gg and gtg) in PE crystallites is confirmed by infrared spectroscopic measurements [32,33], and they are abundant there at high temperatures (see [33] and the comparison between 13 C NMR-and X-ray-determined degree of crystallinity of a PE sample at elevated temperatures ( [34], p. 4335e4336)). However, this fact cannot be regarded as a direct proof for the existence of the above-mentioned conformational defects of a definite type (the simplest one is tg þ tg À tg þ t).…”
Section: Introductionmentioning
confidence: 66%
“…The presence of gauche conformations and some sequences of gauche and trans conformations (for example, gg and gtg) in PE crystallites is confirmed by infrared spectroscopic measurements [32,33], and they are abundant there at high temperatures (see [33] and the comparison between 13 C NMR-and X-ray-determined degree of crystallinity of a PE sample at elevated temperatures ( [34], p. 4335e4336)). However, this fact cannot be regarded as a direct proof for the existence of the above-mentioned conformational defects of a definite type (the simplest one is tg þ tg À tg þ t).…”
Section: Introductionmentioning
confidence: 66%
“…Infrared spectroscopic studies of alkanes and related systems have revealed much regarding the details of conformation and packing arrangements [153][154][155][156][157][158][159][160][161][162][163][164][165][166]. Research focused on the application of this powerful characterization tool to study adsorbed molecules on metal surfaces was being developed by the late 1950s [167].…”
Section: Infrared Reflection Absorption Spectroscopymentioning
confidence: 99%
“…Vibrational spectroscopy has long been used for chemical structure analysis. Infrared spectroscopic studies of alkanes and related systems have revealed much regarding the details of conformation and packing arrangements [153][154][155][156][157][158][159][160][161][162][163][164][165][166]. Research focused on the application of this powerful characterization tool to study adsorbed molecules on metal surfaces was being developed by the late 1950s [167].…”
Section: Infrared Reflection Absorption Spectroscopymentioning
confidence: 99%